Change of limb alignment in Korean children and adolescents with idiopathic genu valgum - Moon, Seo Ho; Kwon, Soon Sun; Park, Moon Seok; Kim, Nak Tscheol; Sung, Ki Hyuk (Medicine (United States), 2021)
There has been no study evaluating the change of limb alignment for patients with genu valgum. The purpose of this study was to investigate the change of limb alignments in children and adolescents with idiopathic genu valgum through evaluating distal femur, proximal tibia, and knee joint line. Consecutive children and adolescents, under the age of 18, with genu valgum were included. Mechanical tibiofemoral angle, mechanical lateral distal femoral angle, mechanical medial proximal tibia angle, and joint line convergence angle were measured. The rate of changes for each radiographic measurement were analyzed using a linear mixed model. A total of 1539 teleroentgenograms from 518 limbs of 273 individuals were included in this study. Linear mixed model showed that the change of limb alignment was significantly associated with age, but not associated with gender and laterality. The mechanical tibiofemoral angle was most valgus initially, decreasing until reaching its lowest value of 2.8° at 10 years old. The mechanical lateral distal femoral angle decreases from initial neutral alignment and increases in valgus continuously. The mechanical medial proximal tibia angle decreases from initial valgus and progresses to be neutral at around the age of 10. The joint line convergence angle decreases sharply from initial valgus alignment to 0° at the age of 5.Valgus alignment in children with idiopathic genu valgum decreases until approximately the age of 10. In younger children, the tibia and joint line contribute most to overall valgus alignment; in older children, the femur contributes the most. Based on our results, we recommend monitoring patient limb alignment until it stabilizes around the age of 10, and then carefully planning and performing corrective surgery with complete consideration of the changing bony alignment.
Keywords: Adolescent; Child; Genu Valgum; Humans; Radiography; Republic of Korea; Retrospective Studies; Tibia; age; children; genu valgum; linear mixed model